Synthesis of High-Aspect-Ratio Nickel Nanowires by Dropping Method - Zhang, Jiaqi (Nanoscale Res Lett, 2016)
A facile and high-yield route, dropping method, has been used to synthesize Ni nanowires (NWs) with a high aspect ratio. Compared to the conventional chemical reduction method, the diameter of Ni NWs prepared by the dropping method distinctively decreased and the surface roughness was improved. After optimizing the process parameters such as the Ni ion concentration and volume of the dropped NiCl(2)·6H(2)O solution, the diameter and aspect ratio of the NWs are 70 nm and ~600, respectively. The possible synthesized process of the dropping method was discussed. This work presents a preferred approach to fabricate high-quality one-dimensional magnetic materials which have potential applications in electrochemical devices, magnetic sensors, and catalytic agents.